Examining Quality of Work Life Factors That Drive Employee Performance Private Hospitals In Bali Province - Noviyanti, Ni Made Dian; Desak Made Febri Purnama Sari (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to identify factors of Quality of Work Life (QWL) that drive employee performance in private hospitals in Bali Province. The background of this study is based on the high demands of the community for the quality of health services and complaints that still often arise regarding services in private hospitals. This study adopts a quantitative approach with factor analysis and hypothesis testing methods. The nine QWL components analyzed include employee involvement, compensation, job security, work environment safety, pride in the institution, career development, facilities, problem solving, and communication. The results of the study indicate that several QWL factors have a significant influence on improving employee performance, both medical and non-medical personnel. These findings provide practical implications for hospital management in designing strategies to improve work welfare in order to improve patient performance and satisfaction. This study also provides theoretical contributions by enriching the study of the relationship between QWL and performance in the context of private health services in tourist destinations.